The Meaning of Village Purification and Worshipping Water Spring as A Ritual To Preserve The Ecological Sustainability of Penanggungan Sites East Java, Indonesia - Hudiyanto, Reza; Lutfi, Ismail (Universitas Negeri Malang, 2020)
This study attempted to describe the correlation between village purification and water spring worshipping – which are held every year by villagers nearby Penanggungan sites, as well as the sustainability of archaeological sites and their surrounding environment. Considering the research object was a cultural phenomenon, qualitative research was applied in describing and analyzing the finding. This research method demanded more detailed information of the sequent events, their components, and meanings. Therefore, we began the research activities by observing, describing, interpreting, and reporting every moment in the rituals. In the second stage, we attempted to correlate between this ritual proceed to the preservation of the water supply. Our research showed that ritual has played an important role in preserving the ecological balance between human beings and nature. When the people believed to the creed that temples and other archaeological objects were home to spiritual power and figured out the last civilization, they would not make any damages to the soil, illegal logging, and a fire in the ridge. Any disturbance to their mountain would give an effect on their means of life since most of the villagers were rice growers. It also proved that there was a connection between popular belief about the sacred place and environment conservation.